Development of an articulate storyline-based learning media to improve competency in determining main idea of informative text for four graders - Eni Yuniarsih; Sukarir Nuryanto (Universitas Muhammadiyah Malang, 2025)
Indonesian language learning at the primary school level requires active student involvement; however, the teacher's limited understanding of current technology results in students struggling to comprehend the material due to the limited use of learning media. This study aims to develop an Articulate Storyline-based learning media that can be accessed and used flexibly by students anytime and anywhere. Researchers used the type of Research and Development (R&D) research using the Borg and Gall model. This research aims to produce articulate storyline learning media for grade IV elementary schools on the main idea of informative text. The results of the articulate storyline media research obtained very good qualifications declared valid and effective as Indonesian language learning media in elementary schools with a percentage of teacher (90,9%) and student responses (95,4%), as well as (87%) from media experts and (93%) from material experts. It was stated in the T-Test <0.05 with a small-scale N-Gain of 0.60 and a large scale of 0.70 so that the articulate storyline media was declared effective and feasible to support Indonesian language learning to improve the competence of determining the main idea of informative text for grade IV students of SD 1 Ngembal Kulon.